185. Despite the Availability of Free Testing and Care Testing for Extragenital Sexually Transmitted Infections in a Cohort of Hiv-infected Department of Defense Beneficiaries Is Low and Similar to the Rates Observed Nationwide. (31st December 2020) - Ganesan, Anuradha; Wang, Xun; Blaylock, Jason M; Okulicz, Jason; Maves, Ryan C; Colombo, Rhonda; Utz, Gregory; Schofield, Christina; Kronmann, Karl; Lalani, Tahaniyat; Garges, Eric; Agan, Brian
Abstract: Background: Background - Current guidelines recommend annual extragenital [EG] testing for all sexually active men who have sex with men (MSM), and every 3−6 months for MSM at risk for sexually transmitted infections (STIs). Compliance with this guideline is low and testing rates among MSM with HIV have ranged between 30–46%. Financial disincentives (such as the lack of reimbursement for EG testing) may contribute to the lower EG testing rates. To examine if access to free testing improves EG testing rates, we used data from the US Military HIV Natural History Study (NHS), a cohort comprised of HIV-infected Department of Defense beneficiaries with access to care and free testing. Methods: Methods - Among NHS participants with a follow-up visit between 1/1/2013 and 1/1/2018, genital (primarily urine samples) and EG testing rates (pharyngeal and rectal) were calculated and temporal trends examined. Multivariate logistic regression analysis was used to examine factors associated with EG testing. In a sub-set of participants who answered a risk behavior survey we examined risk-related information. Results: Results - Of the 1971 male participants who had a NHS visit during the study period, 1962 (99.5%) had genital and 1419 (72%) had EG testing performed at least once. Annual genital and EG testing rates ranged between 96 - 98% and 33% - 46% respectively. No temporal trends were observed in EG testing rates. EG testing rates were higher in those with a history of gonorrhea, chlamydia or syphilis in the year prior, ranging between 50 and 67%. EG testing was more likely to occur in those who were younger and those with a prior history of STI (Table 1). In a subset of participants with risk behavior information, those who reported being MSM were more likely to be tested [Referent heterosexual; Odds Ratio 2.35 [95% CI 1.60–3.46]. Conclusion: Conclusion -Despite the availability of free EG testing, EG testing rates were low in the NHS and similar to those observed nationwide This contrasts with the genital testing rates which were well over 95%, suggesting provider/patient related barriers are likely driving the lower testing rates. To improve testing rates further study is required to fully characterize indications for EG testing and potential provider- and/or patient-related barriers to EG testing. Disclosures: All Authors : No reported disclosures